Viabilidade de sementes de Handroanthus heptaphyllus (Vell.) Mattos armazenadas nos frutos - Martins, Maria Rita Silva Gilli [UNESP] (2013)
The objective of the research was to evaluate the behavior of Handroanthus heptaphyllus (Vell.) MATTOS seeds, stored into the fruits (SF) and by conventional procedure(SC). The fruit and seeds were stored in kraft paper bags by the period of eight months. They were tested through the three different conditions: dry chamber at 20 ° C and 45% RU; cold chamber at 10 º C and 90% RU, and laboratory environment without control of temperature and humidity. We evaluated the seeds by their germination, electrical conductivity, water content of seeds and fruits, soluble protein content, and lipid content and enzyme activity of peroxidase and polyphenoloxidase. It was also measured the size of seeds (length, height, and thickness), for seed lot characterization. Seeds harvested after 120 days of anthesis, showed good germination (83%) and electrical conductivity (40.7 μs.cm-1.g-1), even though with high water content (49.3%). Generally, seeds stored by conventional procedure (SC)presented better results than compared to seeds stored into the fruits the fruit (SF). The values of germination and water content decreased along the time, while the values of electrical conductivity increased. The results for seeds stored in cold chamber were higher than the other storage conditions. There was higher peroxidase activity in fruits than for seeds, into the dry chamber. Among the seeds, the activity in SF seeds was lower when stored in cold chamber. In dry chamber and in environment conditions, the peroxidase activity was lower for SC seeds. The polyphenoloxidase activity was higher in fruit in all of storage conditions, also was higher in SC seeds when in cold chamber and in dry chaqmber until 4th month. Already for environment conditions was lower in SC seeds until the 3rd month of storage. Seeds stored of conventional procedures (SC) had higher levels of lipids in all storage conditions and higher protein ...